Augmented cognition : intelligent technologies : 12th International Conference, AC 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: intelligent technologies : 12th International Conference, AC 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I (2018) - Unknown
No abstract available